Identification of small peptides and glycinamide that inhibit melanin synthesis using a positional scanning synthetic peptide combinatorial library. (1st April 2019) - Kim, J. H.; Seok, J. K.; Kim, Y. M.; Boo, Y. C.
Summary: Background: Antimelanogenic peptides are potentially useful to treat hyperpigmentation, but many peptides have limited application because of high cost and/or low activity. Objectives: To identify small and potent peptide inhibitors of cellular melanin synthesis that are useful for cosmetic and medical applications. Methods: A positional scanning synthetic tetrapeptide combinatorial library was used for screening of potentially active peptides. Antimelanogenic activities of the peptide pools and individual peptides were evaluated in B16‐F10 melanoma cells and human epidermal melanocytes treated with alpha‐melanocyte‐stimulating hormone (α‐MSH). Results: Predicted active tetrapeptide sequences were R‐(F/L)‐(C/W)‐(G/R)‐NH2 . Of the individual tetrapeptides tested, D3 (RFWG‐NH2 ) and D5 (RLWG‐NH2 ) exhibited high antimelanogenic activities. Tetrapeptide D9 (FRWG‐NH2 ) with a sequence identical to that of a portion of α‐MSH also showed antimelanogenic activity. Of the tripeptides tested, E5 (FWG‐NH2 ), E6 (LWG‐NH2 ) and E7 (RWG‐NH2 ) were relatively more active. Dipeptide F1 (WG‐NH2 ) and monopeptide G1 (G‐NH2, glycinamide) retained activity, but G2 (Ac‐G‐NH2 ) and G3 (glycine) did not. The antimelanogenic activities of peptides D3, E5, F1 and G1 were verified in α‐MSH‐stimulated human epidermal melanocytes. Commercially available G‐NH2 ·HCl suppressed the phosphorylation levels of cAMP‐responsive element binding protein, protein levels of microphthalmia‐associated transcription factor and tyrosinase, l ‐tyrosine hydroxylase activity of tyrosinase, and the melanin levels in stimulated cells. Conclusions: Small peptides, including glycinamide and tryptophanyl glycinamide, are potent antimelanogenic agents with potential value for the treatment of skin hyperpigmentation. Abstract : What's already known about this topic? Antimelanogenic peptides are potentially useful for the treatment of hyperpigmentation. What does this study add? The present study identified very small peptides, including glycinamide and tryptophanyl glycinamide, which potently inhibit cellular melanogenesis. What is the translational message? Glycinamide and peptidyl glycinamides regulate cellular melanin synthesis and might be useful for treating skin hyperpigmentation. Linked Comment:  Slominski et al. Br J Dermatol 2019; 181 :17–18 . Plain language summary available online Respond to this article